Thin-Film Photovoltaic Modules Characterisation Based on I-V Measurements Under Outdoor Conditions - Slawomir Gulkowski; Ewelina Krawczak (Energies)
The characterisation of photovoltaic modules requires a specialised laboratory that guarantees precise control of irradiance and its spectrum and control of the module temperature during testing. As an alternative, characteristic parameters can be extracted from the measurements of the current-voltage characteristics (I-V curves) carried out under outdoor conditions. This paper presents the results of the two commercial thin-film photovoltaic modules’ characterisation. The first analysed device was a cadmium telluride (CdTe) photovoltaic module fabricated on glass, while the second was the flexible copper indium gallium diselenide (CIGS) PV module. The main parameters of the PV modules were extracted based on the series of I-V curve measurements under real operating conditions in Poland with the use of the capacitor-based I-V tracer. Solar radiation together with the modules’ temperature were registered simultaneously with the I-V characterisation. Two approaches were proposed to estimate the main PV parameters at standard test conditions as output power, short circuit current or open circuit voltage. The difference in results of power for both approaches was below 1.5%. Energy, computed using the Osterwald model, was compared with the experimental measurements. The best results of absolute relative error (ARE) were found around 0.5% for both technologies. The lowest value of root mean squared error (RMSE) was 1.3% in terms of CdTe technology and 3.1% for CIGS.